Desenvolvimento de materiais cerâmicos inovadores a base de gesso e resíduo para uso na construção civil - Silva, Víctor Valério Landim da (2022)
Civil construction is one of the oldest activities known and the reduction of resources provides an environment of innovation in order to develop methods and products that minimize costs and leverage the production system. The reuse of residues corroborates in the reduction of costs in several stages of the construction process due to the optimization of its use and the reduction of waste and losses. In view of the many negative impacts caused by the accumulation of waste in the environment, environmentally responsible solutions were sought, adapting to the principle of the 5 R's - Rethink, Refuse, Reduce, Reuse, and Recycle. As an alternative to mitigate such problems, we promoted the partial substitution of gypsum (non renewable resource) in the proportions of 5%, 10% and 15% by waste ornamental rocks (marble and granite), using them in the manufacturing process of sustainable plaster blocks and analyzing their properties and characteristics. After the execution of all physical and mechanical tests it was concluded that there were significant increases and improvements in the properties of the sustainable blocks analyzed, regarding: flexural strength, hardness and density. Regarding the water absorption capacity, there was a decrease in the percentage of absorption of sustainable blocks compared to traditional blocks. Therefore, after this study, it was identified that the use of ornamental stone waste in the production process of gypsum blocks presents numerous benefits and its high potential for promoting sustainable innovation is directly observed.